Oxfam Aid to Canada’s First Nations, 1962–1975: Eating Lynx, Starving for Jobs, and Flying a Talking Bird - Marshall, Dominique; Sterparn, Julia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
The first project financed by Oxfam Canada after its incorporation in 1962 was an emergency relief operation towards First Nations in Northern Manitoba, which made national headlines. A decade later, Oxfam Canada funded the floating plane of the Yukon Native Brotherhood, to foster communications between distant First Nations communities of the far north. The ship ended up carrying many of the aboriginal politicians who launched the modern round of reclamations for land claims and aboriginal rights. A close study of the actors and ideas at stake shows how the British-born NGO had to face the disapproval of provincial and federal authorities, and of churches traditionally responsible for Indian welfare, for the embarrassment it brought them. As the British and Canadian humanitarians considered the deeper economic, political and cultural stakes of aboriginal hardships, each step of their interventions called for decisions about the extent and the nature of their involvement in Canada’ Indian policy, the new kind of industrial relations brought to the North by large projects of exploitation of natural resources, and the unequal development of the universal welfare state for First Nations. In turn, these external demands revealed and shaped Oxfam’s very structure of governance, and its own internal debates between charity and justice, neutrality and support for movements of colonial liberation, and the often competing goals of large fundraising and education of the Euro-Canadan public about the global South.